Syncope following Pfizer BioNTech (bnt162b2) vaccination unmasking Brugada syndrome - Mohammad Altermanini (16810755) (2023)
The Brugada syndrome is an uncommon inherited condition associated with increased risk of ventricular tachyarrhythmias and sudden cardiac death. Different triggers including fever are well known to precipitate the Brugada pattern on electrocardiogram. We report a patient who presents with syncope, two days after the first dose of the BNT162b2 vaccine due to fever-related unmasking of Brugada syndrome. Other Information Published in: Heliyon License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.heliyon.2023.e18716